SHURAH AL-MAMDUH WA AL-MADZMUM FI SYI'R AL-MUTANABBI - Wafa Said Shahwan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
This study was aimed at illustrating the Arabic language poet (al-Mutanabbi) with the theme of satire: his satire of Kafur who frustrated al-Mutanabbi's hopes. The study also examined the poem psychologically and rhetorically.The comparative study was built upon the comparison of the existence with the other that raises the inferior and lowers the case of the superior. Therefore, al-Mutanabbi compared between Kafur and others and compared fairly between Kafur and Sayf al-Dawleh until it turned the praised character into a rebuked one under the absence of the addressee (the praised figure) and the presence of the rebuked addressee (the one who is satired). In this study, it was examined the justifications of the transformation from praise to satire which became obvious in many of Al- Mutanabbi's poems which he recited in praising Kafur implicitly and explicitly.DOI: 10.15408/a.v3i2.4039